THE INVESTIGATING STUDENTS’ STRESS MODEL OF THE COGNITIVE LOAD IN UNDERGRADUATE ENGLISH THESIS WRITING: Menyelidiki Model Stres Mahasiswa terhadap Beban Kognitif dalam Penulisan Skripsi Bahasa Inggris Tingkat Sarjana - Sunaryo, Dera Febriyanti Sunaryo; Trisnawati, Winda; Kurniawan, Ridho (Journal Of Language Education and Development (JLed), 2025)
This research title is The Investigating Students’ Stress Model of the Cognitive Load in Undergraduate English Thesis Writing. The purpose of this research is to explore how final-year students who write their English theses while working part-time experience stress in relation to intrinsic, extraneous, and germane cognitive loads, using three stress model approaches: stimulus, response, and transactional stress models.This research uses a qualitative method with a case study approach. The subjects of this study were four English Education students of Universitas Muhammadiyah Muara Bungo who work part-time. Data were obtained through in-depth interviews and analyzed thematically using Maxqda. The results showed that the students experienced stress related to three types of cognitive load: intrinsic cognitive load, such as difficulty understanding theory, limited vocabulary, sentence structure, and translation; extranouse cognitive load, such as confusing lecturer revisions, family pressure, workload, and limited resources; and germane load, which although stressful, encourages motivation, development of coping strategies, and deeper academic understanding. These three load are experienced through stimulus (external pressure), response (emotional and physical reactions), and transactional (individual judgment and adaptive strategies) stress models that vary from student to student.